Quantitative economics as a scientific approach to the solution of problems of a complex nature – in honor of Professor Willem Karel M. Brauers on the occasion of his 90th birthday - Masri, Hatem (Technological and Economic Development of Economy, 2014)
In the previous century Quantitative Economics substantially evolved in the direction of Mathematical Economics, Econometrics and Operational Research. Professor Willem Karel M. Brauers sees it mainly as a scientific approach to the solutions of problems of a complex nature by Methods such as Input-Output Analysis and Multi-Objective Optimization. At the occasion of his 90th birthday this article highlights the research of Professor Willem Karel M. Brauers, presents a review of his extensive scientific work and lists some of his publications.